Pre-Service Teachersâ€™ Experiences in Developing Digital Learning Designs using ADDIE Model Amid COVID-19 Pandemic - Nuryadin, Asep; Lidinillah, Dindin Abdul Muiz; Muharram, Muhammad Rijal Wahid (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to discover pre-service teachersâ€™ experiences in developing digital learning designs during the COVID-19 pandemic. It is expected that the findings of this study can help lecturers, university students, higher education institutions, and other relevant stakeholders in preparing the implementation of learning amid a global pandemic or other relevant crises, especially related to conducting the development of a particular design or product using ADDIE model. The method used in this study was a case study with a descriptive approach. Research subjects or participants involved in this study were 41 pre-service teachers who took a unit named â€œDesain Sistem Pembelajaran Digital or Digital Learning System Designâ€ offered in the sixth semester in Bachelor of Elementary School Teacher Education Study Program, UPI Tasikmalaya Campus. This study results in several findings related to pre-service teachersâ€™ experiences in developing digital learning designs using the ADDIE model amid the COVID-19 pandemic. In addition, this study also has discovered information regarding digital learning designs and digital learning materials/tools developed by the pre-service teachers.